Synthesis of low-size flower-like AlOOH structures; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Bakina O. V. Olga Vladimirovna; Glazkova E. A. Elena Alekseevna; Svarovskaya N. V. Natalia Valentinovna; Lozhkomoev A. S. Aleksandr Sergeevich; Khorobraya E. G. Elena; Psakhie S. G. Sergey Grigorievich (2014, 2014)
Title screen